“Cuidados de enfermería en un paciente geriátrico con diabetes mellitus tipo ll y pie diabético” - Zamora Pizanán, Gladys Milena (2024)
Type 2 diabetes mellitus is a chronic condition characterized by the body's inability to effectively use insulin. In geriatric patients, this disease presents unique challenges due to the interaction of diabetes with other common medical conditions, as they exhibit distinct pathophysiological and clinical characteristics compared to younger diabetic patients. Therefore, this case study focused on the nursing care provided to a 69-year-old geriatric patient with Type 2 Diabetes Mellitus and peripheral circulatory complications, including a limb amputation. The main objective was to analyze the nursing care provided to a geriatric patient with Type 2 Diabetes Mellitus and diabetic foot, considering the clinical aspects involved, in order to identify effective practices that contribute to the prevention and management of this medical condition. Nursing interventions were focused on glucose control, wound care for the left foot, emotional support, and complication prevention. Measures were implemented to keep glucose within target levels, heal the ulcer on the foot, and address the patient's distress and anxiety. A care plan was established that included medication administration, regular wound dressings, and psychological evaluations. As a result of these interventions, there was a significant improvement in the patient's skin integrity, mobility, and emotional well-being. Although the patient still required periodic dressings in the hospital unit, positive progress was made in her healing and rehabilitation process. In conclusion, this case study highlights the importance of a comprehensive approach to the care of geriatric patients with Type 2 Diabetes Mellitus and complications and underscores the need for continuous and personalized care.